Emerging Pollutants from Industrial Emission and Their Health Hazards in Indonesian Seafood: A Review - Dwiyitno Dwiyitno (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2019)
Emerging pollutants (EPs) or contaminants of emerging concern (CECs) have become global awareness since few decades ago, including in Indonesia. Intensive usage of industrial compounds has led to the massive emission to the environment and therefore their potential adverse effects may endanger aquatic organisms and human health. Based on the available literatures, organotins and flame retardants are two main groups of EPs from industrial emission identified in Indonesian seafood, as well as in those worldwide. However, concentration of both EPs group detected in Indonesian seafood is relatively low than that in developed countries and the majority of South East Asian countries. Toxicological studies revealed that EPs emitted from industrial activities have to be concern, as most of the EPs attributed to endocrine disrupting chemicals. Nevertheless, study on the exposure assessment of EPs in Indonesia is very limited. Even though, the concentrations of EPs in Indonesian seafood produce exposure below tolerable daily intake (TDI) to the local consumer, the long term exposures have to be aware due to their possible continues emission and elevating concentration such as shown by flame retardants. Governmental regulation, monitoring programs, and laboratory approach are among issues to be concern in addressing EPs in Indonesia, especially from industrial emission.